I am just a sister: a field study on sister as mother role from Guangdong, China - Feng, Zhuowen; Ye, Yunying; Wang, Haojing; Wang, Jiuling (Frontiers in Psychology, 2024)
This study aimed to explore sister-as-mother (jieximuzhi) roles in families after the implementation of China's universal two-child (quanmianerhai) and three-child policies (saihaizhengce). By conducting in-depth interviews with 10 sisters from Guangdong Province who fit the sister-motherhood profile, this study investigated their motivations for taking on maternal duties, the characteristics of sister-motherhood roles, and the impact of these roles on the sisters. The results revealed that in families with two or more children, sisters passively assume mother-like responsibilities primarily due to biological age differences and parental neglect, as well as their personal initiative to a certain extent. Additionally, the impact of sister-motherhood roles on sisters includes aspects such as time pressure, financial strain, and increased family intimacy. This study elucidated the phenomenon of sister-motherhood roles that emerge with changes in family structure in China while recognizing the diversity of women's roles within the family, appreciating the challenges faced by sisters in sister-motherhood roles, and providing insights into family labor division and education models.